(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Kasihan District in Bantul Regency is a densely populated area that produces an average of 0.6 kg of household waste per person per day. The low level of waste-sorting practices and the limited availability of residual-waste processing facilities contributed to the growing burden on temporary disposal sites (TPS) and the Piyungan landfill. The Environmental Health Model Village (DPKL) of Soragan was established as a clean and healthy environment model, yet it had not been equipped with adequate waste-processing technology. This community service program aims to improve healthy waste-management behaviors among housewives and to reduce the volume of residual waste through education and the application of a community-scale incinerator technology (Soragan Insor). The program was implemented through five stages: socialization, training on healthy behavior and waste sorting, construction and operation of a one-ton-per-day incinerator, mentoring and evaluation, and the establishment of the DPKL Soragan Community Waste Management Team. The results indicated an increase in community awareness, improved waste-sorting practices, and the effectiveness of the incinerator technology in reducing waste volume by 70–80% per day. Evaluation of 25 participants showed that the capacity for communal waste management was in the very good category, with an average score of 4.22, particularly in knowledge (4.25) and environmental awareness (4.40). This program demonstrated that integrating healthy-behavior education, community participation, and appropriate technology effectively improved environmental quality, strengthened community self-reliance, and supported the achievement of SDGs 3 and 11 at the local level.